An efficient 2D hyper chaos and DNA encoding-based s-box generation method using chaotic evolutionary improvement algorithm for nonlinearity - Garipcan, Ali Murat; Aydin, Yilmaz; Ozkaynak, Fatih (Pergamon-Elsevier Science Ltd, 2025)
In this study, an innovative substitution box (s-box) method is proposed, which combines the complexity and unpredictability of chaotic systems with the natural randomness and security features of Deoxyribonucleic Acid (DNA) encoding, in response to the increasing security requirements in the field of modern cryptography. This method, based on the integration of a two-dimensional (2D) hyper-chaotic Vincent map (VM) and DNA encoding techniques, aims to produce secure and high-performance s-boxes. To evaluate the reliability of the s-boxes, fundamental cryptographic criteria such as nonlinearity (NL), strict avalanche criterion (SAC), differential probability (DP), linear approximation probability (LAP), and bit independence criterion (BIC) are considered. Additionally, a novel chaos-based evolutionary optimization algorithm is proposed to optimize the NL criterion of the s-boxes. This algorithm offers a cost-effective and highly efficient alternative compared to classical metaheuristic methods, providing a balanced structure between security and performance. Experimental findings and comparison results demonstrate that the proposed s-boxes offer effective and reliable solutions for modern cryptographic applications, such as secure data transmission and storage. From a broader perspective, the study makes a meaningful contribution to the literature in the field of data security by presenting a high-performancesbox design meeting the security requirements of cryptographic systems and is resilient against current threats.
Keywords: Information security; Hyperchaotic map; DNA encoding; S -box; High nonlinearity; Cryptography